A lightweight anonymous cross-regional mutual authentication scheme using blockchain technology for internet of vehicles. (October 2021) - Meng, Xiangwei; Xu, Jianbo; Liang, Wei; Xu, Zisang; Li, Kuan-Ching
ABSTRACT: The Internet of Vehicles (IoV) is regarded as the application of the Internet of Things (IoT) in transportation. Each vehicle will acts as a separate node on the Internet of Vehicles, which possesses specific ability to collect data and then send the collected data to the network. In this paper, we propose a scheme with the features of lightweight anonymous mutual authentication and key agreement using blockchain technology to obtain the session key. The security of this scheme is proved by formal proof of Burrows–Abadi–Needham (BAN) logic and informal analysis. Besides, the Automated Validation of Internet Security Protocols and Applications (AVISPA) is used to simulate the scheme. Finally, compared with other related schemes, this scheme has superior advantages and efficiency in lightweight characteristics.